Genetic architecture of open-pollinated varieties of pearl millet for grain iron and zinc densities - Kanatti, Anand; Rai, Kedar Nath; Radhika, Kommineni; Govindaraj, Mahalingam (The Indian Journal of Genetics and Plant Breeding, 2016)
Genetic architecture of two commercial open-pollinated varieties of pearl millet (ICTP 8203 and ICMV 221) for grain iron and zinc densities was studied using 160 full-sib progenies each that were developed following North Carolina Design -1 and evaluated for two seasons. Results showed predominantly additive genetic variance and non significant additive gene effect × environment interaction variance compared to large and significant dominance × environment interaction variance for both micronutrients in both populations. This translated into high narrow-sense heritability for Fe (65%) and Zn (86%) in ICTP 8203, and moderate heritability of 45% for both micronutrients in ICMV 221. In comparison, 1000-seed weight, generally assumed to be highly heritable, was predominantly under dominance gene control and had large dominance × environment interaction, giving the narrow-sense heritability estimates of 31% in ICTP 8203 and 13% in ICMV 221. These results, and highly significant and positive correlation observed between Fe and Zn densities, and non-significant correlations of these micronutrients with grain weight suggest that simultaneous selection for Fe and Zn densities in these populations can be effectively made without compromising the grain size.